O estudo eletrofisiológico na estratificação do risco em portadores de doença de Chagas classificados segundo escore de Rassi - Costa, Ieda Prata (2022)
Background: Chronic Chagas Cardiomyopathy (CCC) presents a set of structural alterations that lead to high cardiac morbidity and mortality. Sudden death in CCC presents difficulties in risk stratification. The electrophysiological study (EPS) may provide new risk predictors cardiovascular events in this population. Primary objective: To evaluate the association of EPS changes with the Rassi risk score in patients with CCC. Material and Methods: This is a prospective cohort study that included 59 patients with diagnosed with T. cruzi infection. These patients were submitted to clinical evaluation and complementary exams and classified according to the Rassi score. Subsequently, they underwent EPS with or without the use of antiarrhythmic drugs. The EPS outcome are sinus node dysfunction, severe conduction system disorders - HV >70ms and VT/VF. For statistical analysis, for ordinal qualitative or quantitative variables, the Kruskal-Wallis test was used, for categorical variables, Fisher's exact test was used, with p<0.05 being considered. The Mantel - Haenszel test was used to assess the independence of the variables. Results: A mean age of patients was 58 years being 64.4% male. The mean Rassi score was 8.7+4.5 points, with 39.5% being low-risk patients, 38.9% of intermediate risk and 27.1% of high risk. 10.2% had NYHA III/IV FC. Low QRS voltage was revealed in 30.5%, 49.2% had cardiomegaly, 61% had NSVT and 62.7% had segmental or global left ventricular (LV) alteration. The EEF was altered in 57.6% of the patients, 3.4% due to DNS, 6.8% due to prolonged VH and 52.5% due to VT/VF. EPS altered in 35% of the low group, 60.9% of the intermediate group and 81.3% of the high risk group (p=0.02). The EPS was altered in 71.1% patients with and 33.3% without syncope and/or pre-syncope (p=0.015); the odds ratio for EPS outcome was estimated at 2.4544 (95%CI: 1.2-4.9; p=0.012). Patients with NSVT on Holter showed 57.1% altered EPS and 58.3% without NSVT (p=0.96). There was association between an low EF and EPS outcome EF<40% had 80% of outcomes in the EEF (p = 0.04) and 70% with LV segmental alterations had altered EF (p=0.01). There was no association between VT and the presence of LV aneurysm (p=0.30). QRS width (p=0.2) and QRS low voltage (p=0.32) did not influence EEF outcomes. Conclusions: Changes in EPS in patients with CCC are associated with progression of the Rassi score. The presence of syncope/pre-syncope was a predictor of negative EEF outcomes independent of Rassi risk. There was association between an low EF and LV segmental alterations with EPS outcome The clinical variables presence of left ventricular aneurysm and NSVT on Holter, low QRS voltage and width QRS did not correlate with outcomes in the EEF.